2020
DOI: 10.1002/ar.24378
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Resibufogenin inhibited colorectal cancer cell growth and tumorigenesis through triggering ferroptosis and ROS production mediated by GPX4 inactivation

Abstract: Resibufogenin (RB) has been used for cancer treatment, but the underlying mechanisms are still unclear. This study aimed to investigate the effects of RB treatment on colorectal cancer (CRC) cells, and to determine the underlying mechanisms. The cell counting kit‐8 assay was used to determine cell viability. Cell morphology was observed under light microscopy, and terminal deoxynucleotidyl transferase‐mediated dUTP nick‐end labeling assay was employed to detect cell apoptosis. Intracellular ferrous iron (Fe2+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…It is capable of reducing the toxic, membranous lipid hydroperoxides into non-toxic lipid alcohols ( Brigelius-Flohé and Maiorino, 2013 ; Yang et al, 2014 ). Increasing GPX4 has been shown to be beneficial in many models of disease by inhibiting ferroptosis ( Lan et al, 2020 ; Shen et al, 2020 ). However, knockdown or inactivation of GPX4 contributes to the accumulation of lipid peroxidation and initiation of ferroptosis ( Park et al, 2019 ; Ye et al, 2020 ).…”
Section: Discovery and Mechanisms Of Ferroptosismentioning
confidence: 99%
“…It is capable of reducing the toxic, membranous lipid hydroperoxides into non-toxic lipid alcohols ( Brigelius-Flohé and Maiorino, 2013 ; Yang et al, 2014 ). Increasing GPX4 has been shown to be beneficial in many models of disease by inhibiting ferroptosis ( Lan et al, 2020 ; Shen et al, 2020 ). However, knockdown or inactivation of GPX4 contributes to the accumulation of lipid peroxidation and initiation of ferroptosis ( Park et al, 2019 ; Ye et al, 2020 ).…”
Section: Discovery and Mechanisms Of Ferroptosismentioning
confidence: 99%
“…b-elemene and cetuximab, which were combined to treat KRAS mutant CRC cells, could induce ferroptosis (Chen et al, 2020). Shen et al demonstrated that RB could inactivate GPX4 to trigger ferroptosis in CRC cells, which can inhibit the growth of CRC cells and tumor formation (Shen et al, 2020).…”
Section: Colorectal Carcinomamentioning
confidence: 99%
“…Shen et al. demonstrated that RB could inactivate GPX4 to trigger ferroptosis in CRC cells, which can inhibit the growth of CRC cells and tumor formation ( Shen et al., 2020 ).…”
Section: The Link Between Ferroptosis and Cancermentioning
confidence: 99%
“…The third major target is the selenoenzyme GPx4. Different inhibitors of GPx4 induce ferroptosis such as RLS3, FIN56, and ML210 (24) and more recently, resibufugenin (62). Postchemotherapy-"persister" cells resistant to lapatinib treatment in breast, melanoma, lung, and ovarian cancer have been characterized as GPx4-dependent (63).…”
Section: Glutathione-dependent Ferroptosismentioning
confidence: 99%